LITERATURE REVIEW ANALISIS HUBUNGAN KEPATUHAN PENGGUNAAN OBAT ANTIASMA DENGAN KUALITAS HIDUP PASIEN ASMA - sayyidah sayyidah; Ayu Werawati; Firdha Senja Maelaningsih; Anis Dwi Kristiyowati (PHRASE (Pharmaceutical Science) Journal, 2023)
Asthma is a chronic inflammatory disease that causes blockage of the respiratory tract which is characterized by wheezing, coughing and a feeling of tightness in the chest that occurs repeatedly, especially at night or in the early morning. The purpose of this study was to identify the characteristics of drug use based on sex and smoking status and to identify the use of anti-acid drugs with the quality of life of asthma patients. The method used in this study uses a literature review research method by collecting various sources obtained from several research articles originating from Google Scholar both national journals. The number of articles used is 5 journals. Based on the results of a literature review that has been carried out, there is evidence of adherence to asthma medication and the quality of life of hige school patients grouped into high quality oflife by 60%, while 44,1%. With dherence to asthma patients, the higer adherence to asthma medication. Then the better qulity of life ppatients asthma.